The mechanisms and factors that induce trained immunity in arthropods and mollusks - Zhao, Mingming; Lin, Zhongyang; Zheng, Zhihong; Yao, Defu; Yang, Shen; Zhao, Yongzhen; Chen, Xiuli; Aweya, Jude Juventus; Zhang, Yueling (Frontiers in Immunology, 2023)
Besides dividing the organism’s immune system into adaptive and innate immunity, it has long been thought that only adaptive immunity can establish immune memory. However, many studies have shown that innate immunity can also build immunological memory through epigenetic reprogramming and modifications to resist pathogens’ reinfection, known as trained immunity. This paper reviews the role of mitochondrial metabolism and epigenetic modifications and describes the molecular foundation in the trained immunity of arthropods and mollusks. Mitochondrial metabolism and epigenetic modifications complement each other and play a key role in trained immunity.